The natural history of amphiblans and reptiles in Sabah - Inger, Robert F. (natural History Publications (Borneo), 1996)
Pp. 101, 130 color photos and a few text-figures, 1 full page map. Color pictorial stiff wrappers, 8vo. This volume is a review of the rich herpetofauna of Borneo, including some of its less conspicuous and sometimes reviled members (from the front wrapper flap). Signed by both authors on the title page above their printed names. No ownership marks and no signs of use.